Rapid single-chip secure processor prototyping on the Open SPARC FPGA platform - Szefer, J.; Zhang, W.; Chen, Y.; Champagne, D.; Chan, King-Sun; Li, W.; Cheung, R.; Lee, R. (2011)
Secure processors have become increasingly important for trustworthy computing as security breaches escalate. By providing hardware-level protection, a secure processor ensures a safe computing environment where confidential data and applications can be protected against both hardware and software attacks. In this paper, we present a single-chip secure processor model and demonstrate rapid prototyping of the secure processor on the OpenSPARC FPGA platform. OpenSPARC T1 is an industry-grade, open-source, FPGA-synthesizable general-purpose microprocessor originally developed by Sun Microsystems, now acquired by Oracle. It is a multi-core, multi-threaded 64-bit processor with open-source hardware, including the microprocessor core, as well as system software that can be freely modified by researchers. We modify the OpenSPARC T1 processor by adding security modules: an AES engine, a TRNG and a memory integrity tree. These enhancements enable security features like memory encryption and memory integrity verification. By prototyping this single-chip secure processor on the FPGA platform, we find that the OpenSPARC T1 FPGA platform has many advantages for secure processor research. Our prototyping demonstrates that additional modules can be added quickly and easily and they add little resource overhead to the base OpenSPARC processor. © 2011 IEEE.